The Political Trust of People towards Local Politicians in Loei Province - Sumano, Phra Kaison; Promgun, Suraphon; Huadsri, Chanchai (Academic MCU Buriram Journal, 2021)
The objectives of this research were: 1) to study the level of the political trust of people towards the local politicians in Loei Province, 2) to study the level of opinion of the people towards the Four Sangahavatthu Dhammas (Bases of Social Solidarity) of the local politicians in Loei Province, 3) to compare the political trust of the people towards the local politicians and 4) to study the guideline to build the political trust of the people towards the local politicians based the people opinions towards the practice according to the Four Sangahavatthu Dhammas of the local politicians in Loei Province. There were 400 sample and 8 key informants in this research. The tools using in this research were the questionnaire and interview form. The obtained data were interpreted by the social sciences computer programme together with the content and context analysis. The research results were as follows: 1) The levels of the political trust of people towards the local politicians in Loei Province in overall and in the studied aspects were at a high level, 2) the levels the practice of the Four Sangahavatthu Dhammas of the local politicians in Loei Province in overall and in the studied aspects were at a high level, 3) the comparative results indicated that the people with difference in the level of their education had their political trust differently with the statistical significance level of 0.05 but those with differences in gender, age, status, occupation and monthly income had their political trust indifferently. According to the people opinions, the people is the political trust differently with the statistical significance level of 0.05 and 4) the guideline to build the political trust of the people is that more tourist attractions should be developed, giving items to help people who have been in need, should be constantly made and the politicians must continually participate in community and social development.